Effects of Y2O3 additives and powder purity on the densification and grain boundary composition of Al2O3/SiC nanocomposites - Shapiro, I; Todd, R; Titchmarsh, J; Roberts, S (2009)
Sub-micron sized SiC additions can be used to increase the wear resistance and change the fracture mode of Al2O3. However, these additions also restrict sintering. Al2O3 and Al2O3-5%SiC 'nanocomposites' were prepared from alumina powders of high purity and of commercial-purity, with or without the addition of Y2O3. The effects of these compositional variables on sintering rate, final density and grain boundary composition were investigated. A direct comparison with Al2O3-SiO2 composites was also made, as it has been proposed that SiC partially oxidises during processing of Al2O3-SiC nanocomposites. The addition of 5 vol.% SiC to Al2O3 hindered densification, as did addition of 0.15 wt.% Y2O3 or 0.1 wt.% SiO2. In contrast, the addition of 0.15 wt.% Y2O3 to Al2O3-5% SiC nanocomposites improved densification. The composition of Al2O3-Al2O3 grain boundaries in these materials was studied using STEM and EDX microanalysis. The addition of SiC and SiO2 caused segregation of Si, and Y2O3 addition caused segregation of Y. The segregation of each element was equivalent to <10% of a monolayer at the grain boundary. However, if SiC and Y2O3 were simultaneously added the segregation increased to 40% of a monolayer. The enhanced segregation was attributed to increased oxidation of SiC in the presence of Y2O3 allowing formation of a SiO2-Al2O3-Y2O3 eutectic phase or a segregated layer which may explain the improvement in sintering rate when Y2O3 was added to nanocomposites. © 2008 Elsevier Ltd. All rights reserved.